Potential of Natural Compounds and Biological Products as HMG-CoA Reductase Enzyme Inhibitors: a Literature Study - Annisa Zahra Rahmayati; Andrey Kusuma Maulana; Aulia Zahra Annabilah; Ayu Paramitha Salsabilla; Camelia Dwiyanti Prasetya; M. Iqbal Rhamadianto (Jurnal Multidisiplin Sahombu, 2025)
HMG-CoA Reductase is a primary target in hypercholesterolemia therapy due to its role in cholesterol biosynthesis in the liver. This study aims to review the potential of natural substances, microbes, and in silico approaches in identifying HMG-CoA Reductase inhibitor compounds. The review was conducted on 10 national and international journals using methods such as molecular docking, enzymatic activity analysis, in silico toxicity validation, and epidemiological studies. The results show various compounds from plants such as Piper crocatum, Allium sativum, Syzygium polyanthum, as well as fermented products like Lactobacillus acidophilus have high potential as inhibitors of this enzyme. Combination therapy, modification of statin compounds, and educational approaches for patients also contribute to the effectiveness of cholesterol therapy.